2023
DOI: 10.1021/acscatal.2c05201
|View full text |Cite
|
Sign up to set email alerts
|

Polaritonic Chemistry: Band-Selective Control of Chemical Reactions by Vibrational Strong Coupling

Abstract: deciding the reaction channel, are probed/can be probed under VSC conditions. We hope that with further progress in the field, one can unambiguously distinguish the results, errors, and uncertainties associated with the measurement conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Referred to plasmon-induced reactions in nanoconfined space, the strong coupling of molecules with plasmon frequency in plasmonic nanocavities (such as NPs on mirrors) offers interesting possibilities to manipulate chemical bond evolution and modify photochemistry. 79 In 2016, Baumberg and coworkers demonstrated that a plasmonic nanocavity containing an MB dye molecule can result in strong single-molecule coupling between the emitter and the plasmon (Figure 9e). 80 Soon after, Feist et al showed that strong coupling of organic molecules to a confined light mode can be used to strongly suppress photoisomerization.…”
Section: Nanoconfined Plasmon-mediated Spatial Selective Reactionmentioning
confidence: 99%
“…Referred to plasmon-induced reactions in nanoconfined space, the strong coupling of molecules with plasmon frequency in plasmonic nanocavities (such as NPs on mirrors) offers interesting possibilities to manipulate chemical bond evolution and modify photochemistry. 79 In 2016, Baumberg and coworkers demonstrated that a plasmonic nanocavity containing an MB dye molecule can result in strong single-molecule coupling between the emitter and the plasmon (Figure 9e). 80 Soon after, Feist et al showed that strong coupling of organic molecules to a confined light mode can be used to strongly suppress photoisomerization.…”
Section: Nanoconfined Plasmon-mediated Spatial Selective Reactionmentioning
confidence: 99%
“…21,22 Indeed, most previous studies have been performed using cavities made of stainless steel cells with high-stiffness spacer. [23][24][25][26][27] This approach is intuitive, but it is not flexible for easy tuning of the cavity mode and other experimental parameters.…”
Section: Introductionmentioning
confidence: 99%
“…If the exchange process is faster than other dissipation rates, it results in the formation of new hybrid states-polaritonic states separated by Rabi splitting energy. [1][2][3] This process becomes more intriguing if an Avogadro number of molecules are collectively coupled to the cavity mode. Collective coupling results in large Rabi splitting energy that can reshuffle the chemical and physical properties of the associated system.…”
Section: Introductionmentioning
confidence: 99%
“…Strong coupling occurs when a confined photon interacts with a molecular transition. If the exchange process is faster than other dissipation rates, it results in the formation of new hybrid states‐polaritonic states separated by Rabi splitting energy [1–3] . This process becomes more intriguing if an Avogadro number of molecules are collectively coupled to the cavity mode.…”
Section: Introductionmentioning
confidence: 99%